Phytochemical Screening and Pharmacological Study of Aegle Marmelos : A Review (International Journal of Scientific Research in Science and Technology, 2024)
Aegle marmelos, commonly called "Bael," is a native Indian herb. The Bael tree—also referred to as the golden apple or Bengal quince—belongs to the Rutaceae family of medium-sized deciduous trees. Traditional medicine has traditionally utilized all portions of the sapling, including the fruit, woof, roots, leaves, and stems because they all have medicinal properties. Regardless of how old the fruit is, this is accurate. The composition of Aegle marmelos has been found to include flavonoids, fatty acids, carbohydrates, tannins, alkaloids, terpenoids, vitamins, and essential oils, among other things. The plant has pharmacological properties that can modulate the immune system, relieve pain, reduce inflammation, treat arthritis, lower blood cholesterol, fight cancer, fight viruses, treat ulcers, and promote wound healing. Its other properties include anti-proliferative, hepatoprotective, antidiabetic, antibacterial, and antifungal properties. Therefore, those who are keen to carry out further research on.